Subcortical atrophy and perfusion patterns in Parkinson disease and multiple system atrophy. (March 2020) - Erro, Roberto; Ponticorvo, Sara; Manara, Renzo; Barone, Paolo; Picillo, Marina; Scannapieco, Sara; Cicarelli, Giulio; Squillante, Massimo; Volpe, Giampiero; Esposito, Fabrizio; Pellecchia, Maria Teresa
Abstract: Background: The clinical differentiation between Parkinson disease (PD) and multiple system atrophy (MSA) is difficult. Objectives: Arterial spin labeling (ASL) is an advanced MRI technique that obviates the use of an exogenous contrast agent for the estimation of cerebral perfusion. We explored the value of ASL in combination with structural MRI for the differentiation between PD and MSA. Methods: Ninety-four subjects (30 PD, 30 MSA and 34 healthy controls) performed a morphometric and ASL-MRI to measure volume and perfusion values within basal ganglia and cerebellum. A region-of-interest analysis was performed to test for structural atrophy and regional blood flow differences between groups. Results: MSA patients showed higher subcortical atrophy than both PD patients and HC, while no differences were observed between the latter. MSA and PD showed lower volume-corrected perfusion values than HC in several cerebellar areas (Crus I, Crus II, right VIIb, right VIIIa, right VIIIb), right caudate and both thalami. MSA and PD patients displayed similar perfusion values in all aforementioned areas, but the right cerebellar area VIIIb (lower in MSA) and right caudate and both thalami (lower in PD). Similar results were obtained when comparing PD and MSA patients with the parkinsonian variant. Conclusions: A perfusion reduction was equally observed in both MSA and PD patients in cerebellar areas that are putatively linked to cognitive (i.e., executive) rather than motor functions. The observed hypo-perfusion could not be explained by atrophy, suggesting the involvement of the cerebellum in the pathophysiology of both MSA and PD. Highlights: Arterial spin labeling is a modern MRI technique for estimating cerebral perfusion. MSA and PD have lower perfusion values than controls in several cerebellar areas. Few differences could be seen in terms of perfusion between MSA and PD. Lower cerebellar perfusion can be linked to cognitive rather than motor dysfunction.